2021
DOI: 10.1098/rsos.200974
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin improves adipocytes browning and mitochondrial function in 3T3-L1 cells and obese rodent model

Abstract: Accumulating evidence suggests that mitochondrial dysfunction and adipocyte differentiation promote lipid accumulation in the development of obesity and diabetes. Curcumin is an active ingredient extracted from Curcuma longa that has been shown to exhibit antioxidant and anti-inflammatory potency in metabolic disorders. However, the underlying mechanisms of curcumin in adipocytes remain largely unexplored. We studied the effects of curcumin on adipogenic differentiation and mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…A study in mice showed that a very high-fat diet (VHFD) supplemented with curcumin (0.7% w/w) for 13 weeks led to a reduction in body weight gain and body fat, along with an increase in lean body mass (114). However, in disagreement with other studies (115), the same authors did not find any effect of curcumin on adipocyte cell size (114). On the other hand, other studies reported no effects of dietary curcumin on body weight and adiposity, in mice (116).…”
Section: Effects On Body Weight and Obesitymentioning
confidence: 92%
See 1 more Smart Citation
“…A study in mice showed that a very high-fat diet (VHFD) supplemented with curcumin (0.7% w/w) for 13 weeks led to a reduction in body weight gain and body fat, along with an increase in lean body mass (114). However, in disagreement with other studies (115), the same authors did not find any effect of curcumin on adipocyte cell size (114). On the other hand, other studies reported no effects of dietary curcumin on body weight and adiposity, in mice (116).…”
Section: Effects On Body Weight and Obesitymentioning
confidence: 92%
“…More recently, curcumin also enhanced the browning process as well as mitochondrial respiratory function in 3T3-L1 cells. These effects have been suggested to be related to stimulatory effects on PPAR, UCP-1, PR domain protein 16 (PRDM16), and PPAR coactivator-1 (PGC-1 expression levels (115).…”
Section: Effects On Body Weight and Obesitymentioning
confidence: 99%
“…In addition, curcumin can induce the beiging of white adipocytes, which was shown in 3T3-L1 cells, but more importantly, in the primary white adipocytes from rats [127] (Figure 2). Moreover, in some of the in vivo models, upregulation of UCP1 as a sign of beiging was observed with or without a cold stimulus [124,128] (Figure 2). Interestingly, studies in lean animals or cells derived from them showed divergent effects of curcumin on beiging in different WAT depots.…”
Section: Effects Of Curcumin On Adipose Tissue and Obesitymentioning
confidence: 98%
“…The AMPK signalling pathway is also involved in the BAT activation stimulated by many natural product ingredients, such as resveratrol, curcumin 134 , EGCG 167 and berberine 154 . Resveratrol is a phenylpropanoid present in various foods including red cabbage, spinach, berries, red wine, and peanuts.…”
Section: Potential Therapeutic Applications In Batmentioning
confidence: 99%
“…Further research is needed to understand the anti-obesity mechanism of natural products in terms of thermogenesis. A growing number of natural products, such as curcumin 134 , thymol 145 , magnolol 144 and albiflorin 146 , have been shown to improve obesity by affecting the thermogenesis of brown adipose tissue through a variety of signalling pathways, and we will not go into detail here. With the development of methods and technologies, the mysteries of thermogenic pathways and their integration and control have begun to become apparent.…”
Section: Potential Therapeutic Applications In Batmentioning
confidence: 99%